DEVILS: cosmic evolution of SED-derived metallicities and their connection to star formation histories. Issue 4 (26th October 2022) - Thorne, Jessica E; Robotham, Aaron S G; Bellstedt, Sabine; Davies, Luke J M; Cook, Robin H W; Cortese, Luca; Holwerda, Benne; Phillipps, Steven; Siudek, Malgorzata
ABSTRACT: Gas-phase metallicities of galaxies are typically measured through auroral or nebular emission lines, but metallicity also leaves an imprint on the overall spectral energy distribution (SED) of a galaxy and can be estimated through SED fitting. We use the ProSpect SED fitting code with a flexible parametric star formation history and an evolving metallicity history to self-consistently measure metallicities, stellar mass, and other galaxy properties for $\sim 90\, 000$ galaxies from the Deep Extragalactic VIsible Legacy Survey (DEVILS) and Galaxy and Mass Assembly (GAMA) survey. We use these to trace the evolution of the mass–metallicity relation (MZR) and show that the MZR only evolves in normalization by $\sim 0.1\, $ dex at stellar mass $M_\star = 10^{10.5}\, M_\odot$ . We find no difference in the MZR between galaxies with and without SED evidence of active galactic nuclei emission at low redshifts ($z$ < 0.3). Our results suggest an anticorrelation between metallicity and star formation activity at fixed stellar mass for galaxies with $M_\star \gt 10^{10.5}\, M_\odot$ for $z$ < 0.3. Using the star formation histories extracted using ProSpect we explore higher order correlations of the MZR with properties of the star formation history including age, width, and shape. We find that at a given stellar mass, galaxies with higher metallicities formed most of their mass over shorter time-scales, and before their peak star formation rate. This work highlights the value of exploring the connection of a galaxy's current gas-phase metallicity to its star formation history in order to understand the physical processes shaping the MZR.